Gut Microbiota: A Novel Therapeutic Target for Parkinson’s Disease - Zhu, Manlian; Liu, Xia; Ye, Yiru; Yan, Xiumei; Cheng, Yiwen; Zhao, Longyou; Chen, Feng; Ling, Zongxin (Frontiers in Immunology, 2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease characterized by motor dysfunction. Growing evidence has demonstrated that gut dysbiosis is involved in the occurrence, development and progression of PD. Numerous clinical trials have identified the characteristics of the changed gut microbiota profiles, and preclinical studies in PD animal models have indicated that gut dysbiosis can influence the progression and onset of PD via increasing intestinal permeability, aggravating neuroinflammation, aggregating abnormal levels of α-synuclein fibrils, increasing oxidative stress, and decreasing neurotransmitter production. The gut microbiota can be considered promising diagnostic and therapeutic targets for PD, which can be regulated by probiotics, psychobiotics, prebiotics, synbiotics, postbiotics, fecal microbiota transplantation, diet modifications, and Chinese medicine. This review summarizes the recent studies in PD-associated gut microbiota profiles and functions, the potential roles, and mechanisms of gut microbiota in PD, and gut microbiota-targeted interventions for PD. Deciphering the underlying roles and mechanisms of the PD-associated gut microbiota will help interpret the pathogenesis of PD from new perspectives and elucidate novel therapeutic strategies for PD.